Analisis Kesalahan Siswa Dalam Menyelesaikan Soal-Soal Perbandingan Trigonometri di Kelas X SMA Negeri 1 Ratahan - Tania Gloria Sualang; Jorry Ferry Monoarfa; Derel F. Kaunang (Journal on Education, 2024)
This research aims to analyze high school students' errors in solving trigonometry comparison problems based on Newman's theory. The type of research used is qualitative research using descriptive methods. The subjects of this research were class XG students at SMA Negeri 1 Ratahan with a total of 28 students. The instrument used in this research was 4 trigonometry comparison essay questions. The results of this research show that the most frequent errors made by students in solving trigonometry comparison questions are errors in writing the final answer with an error percentage of 40.17%, followed by process skills errors with an error percentage of 28.57%, then transformation errors with the percentage of errors was 9.82%, and the percentage of errors in understanding was 9.82%.